The effect of positive inter-group contact on cooperation: the moderating role of individualism - Xiao, Rikui; Li, Shuxin (Frontiers in Psychology, 2024)
The effects of intergroup contact on cooperation are well documented, but less is known about cultural moderators of this relationship. Contributing to the literature, we examined whether cultural orientation moderates the effect of positive intergroup contact on cooperation, and place emphasis on individualism. By creating a game-cooperation situation by the trust game paradigm, 322 Taiwan youth were involved in the study and completed the positive intergroup contact scale, individual-collectivism scale and social distance scale. The results show that: (1) positive intergroup contact effectively promotes cooperative behavior; (2) Taiwan youth who has closer social distance with mainland youth demonstrates higher levels of cooperative behavior after group interactions than lager social distance.; (3) Individualism has a significant moderation role in the relationship between positive inter-group contact and cooperation. The effect of positive inter-group contact on cooperation became stronger in less individualistic group. The effect of social distance on cooperation became stronger in less individualistic group. Cultural orientation represented by individualism is proved to be one moderator of the intergroup contact-cooperation relationship..